Першовідкривачі донецького вугілля - Гайко, Геннадій Іванович; Білецький, Володимир Стефанович (Український культурологічний центр, 2016)
У статті проведено аналіз архівних документів і літературних джерел щодо відкриття й початку промислового освоєння Донецького вугільного басейну. Розкрита роль населення Східної України й місцевих еліт в опануванні перших вугільних родовищ. Показано внесок Карла Гаскойна та інженерів його команди в будівництво першої вугільної шахти й становлення системних геологічних досліджень на сході України.

The analysis of archival documents and literature on early discovery and commercial development of the Donetsk coal basin. The role of the population of Eastern Ukraine and local elites in learning first coal deposits. Opening of Donbass coal - much politicized issue in the Soviet era. Modern analysis of archival documents and literary sources, summarizing data on coal discovery reveals that the following: Most likely, the population of Eastern Ukraine-Rus (later - land Zaporizhian Sich) opened the Donbas coal availability empirically - through practical collisions to the XVIII century. At the beginning of the XVIII century. search for coal in the Donbas intensified due to the salt pans - evaporation of salt water and Tor and Bahmutskiy lakes and wells for brine sampling. In 1721, Nikita Vepreyskyy-Managing Bahmutskiy salt mines, landrat, nobleman and Simon Chirkov-Bahmutskiy fortress commandant took samples of coal in two places - in the tract Skelevate and on the White river. Coal samples were sent to St. Petersburg in the Mining College (received 20 January 1722). Their tests showed high quality coal. The first coal trade was organized in 1723 by the same M. Vepreyskyy and S.Chirkov. In the coal mining and fishing during August-September 1723 were about 200 people unemployed. Coal is found using both the salt and in the forge - itwas the first mine and the first industrial use of coal Donbass. Priority official opening of coal Vepreyskyy and Chirkov official confirmed reports of special expedition leader G. Nixon to the Mining Board (from May 25, 1725). Ore maker G. Kapustin not related to the discovery of coal in the Donbas. According to official reports mentioned a special expedition leader G. Nixon, H. Kapustin was not even in the Donbass. Start the industrial Donbass in the second half and especially the end of the XVIII century. and is closely linked to the needs of uncovered new deposits of coal and mass for the purposes of the first Black Sea Fleet steamer, and then - for use in the metallurgical process. A special role in the industrial development of Donbass coal and steel as the region played a Scottish engineer Charles (Charles) Gascoyn (1737-1806), director at the time the largest in the world Karronsky Ironworks. All mines, mines and geological party Donbass were attributed to the Lugansk plant and report directly K. Gascoyn. This contributed to the intensive development of themining industry in the region.
The discoverer of the Donetsk coal
Keywords: Донецький басейн; пріоритет відкриття; рудознавець; геологічна експедиція; вугільне родовище; перша вугільна шахта; кокс; ливарний завод; Donetsk Basin; priority of discovery; оre maker; geological expedition; coal mine; first mine coal; coke; foundry